2013
DOI: 10.4236/ns.2013.510134
|View full text |Cite
|
Sign up to set email alerts
|

Effect of natural and synthetic growth stimulators on <i>in vitro</i> rooting and acclimatization of common ash (<i>Fraxinus excelsior</i> L.) microplants

Abstract: Application of growth stimulators can be especially effective on plantlets in vitro of tree species which are usually worse rooted and adapted in comparison with annual plants. In our work we evaluate effects of natural (dihydroquercetin, Zircon) and synthetic growth stimulators (Melafen, Fumar, Epin-Extra) on rooting and acclimatization of common ash (Fraxinus excelsior L.) microplants. The 0.05%-0.2% Zircon and 10 −5 % Melafen enhanced in vitro rooting by 29%-37% and 31%, respectively. Melafen also stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…) and epicotyl, leaf and root tissue (Hammatt ; Mitras et al . ; Lebedev & Schestibratov ). Shoot tips can be cryopreserved (Schoenweiss, Meier‐Dinkel & Grotha ).…”
Section: Structure and Physiologymentioning
confidence: 96%
See 1 more Smart Citation
“…) and epicotyl, leaf and root tissue (Hammatt ; Mitras et al . ; Lebedev & Schestibratov ). Shoot tips can be cryopreserved (Schoenweiss, Meier‐Dinkel & Grotha ).…”
Section: Structure and Physiologymentioning
confidence: 96%
“…Ash is also readily propagated in vivo. Adventitious shoot regeneration has been reported from excised embryos for F. excelsior (Mockeliunaite & Kuusiene 2004;Capuana et al 2007) and epicotyl, leaf and root tissue (Hammatt 1994;Mitras et al 2009;Lebedev & Schestibratov 2013). Shoot tips can be cryopreserved (Schoenweiss, Meier-Dinkel & Grotha 2005).…”
Section: ( B ) M Y C O R R H I Z Amentioning
confidence: 99%
“…It was reported that the plantlets were able to form roots invitro on a WPM based media supplemented with IBA or NAA (0.2-0.8ppm), which induced roots on 62-84% of the plantlets within 2-3 weeks, with 72-94% of the rooted plantlets surviving transplantation into pots, but very few details other than this were provided. Some authors succeeded in establishing shoots into culture directly from mature ash trees, usually from grafted material growing under cover (Silveira and Cottignies 1994;Hammatt 1994;Schoenweiss and Meier-Dinkel 2005;Douglas et al 2013;Schestibratov 2013 and2016;Šedivá et al 2017). Various permutations of basal salts and phytohormones for stimulating shoot formation from assorted ash starter material have been tested, usually cultivated at ~24 o C and ~50µm/m 2 /s -1 of photosynthetically active light.…”
Section: Introductionmentioning
confidence: 99%
“…Ash seedlings have been shown to be an excellent source of material for establishing in-vitro shoot cultures (Hammatt and Ridout 1992;Tabrett and Hammatt 1992;Raquin et al 2002;Schoenweiss and Meier-Dinkel 2005;Mitras et al 2009;Lebedev and Schestibratov 2013;Dancheva and Iliev 2015;Šedivá et al 2017), meaning that shoot cultures can be established from seeds held in archives such as the Millennium Seed Bank (Clark and Webber 2017). Hammatt and Ridout (1992) established a small number of ash shoot cultures from explants taken from germinating sterilised seeds, collected from a single unspecified ash tree, as did Tabrett and Hammatt (1992).…”
Section: Introductionmentioning
confidence: 99%
“…These factors resulted in the formation of heterotrophic and photomixotrophic plantlets with altered morpho‐physiology and anatomy, such as poorly developed photosynthetic tissues, nonfunctional stomata, underdeveloped‐cuticle, −epidermal and ‐subepidermal layers, unorganized cells, reduced vascular elements, etc. (Lamhamedi, Chamberland, & Tremblay, 2003; Lebedev & Schestibratov, 2013). Such plants could not resist the biotic and abiotic factors of harsh environments upon ex vitro and field transfer (Hazarika, Parthasarathy, Nagaraju, & Bhowmik, 2000; Pospisilova, Synkova, Haisel, & Semoradova, 2007).…”
Section: Introductionmentioning
confidence: 99%